2017
DOI: 10.4314/ijbcs.v10i4.39
|View full text |Cite
|
Sign up to set email alerts
|

Combination of alum and extracted <i>Moringa oleifera</i> bioactive molecules powder for municipal wastewater treatment

Abstract: Most of wastewater treatment stations use aluminum sulfate (Al 2 (SO 4 ) 3 , 18H 2 O) and ferric sulfate (Fe 2 (SO 4 ) 3 ) despite their relatively high cost. High turbidity of wastewater constitutes also a limit for a good treatment and increases the cost of the treatment. Moringa oleifera (MO) seeds are well known to have the ability to reduce turbidity and Chemical Oxygen Demand (COD) of wastewater. Moreover, most of the studies focus on using seeds directly for that purpose increasing consequently organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…Therefore, there was no significant difference for turbidity removal between 150 and 200 mg/L of MO. These results are similar to those obtained by Kayode et al [32], Kane et al [33], and Boulaadjoul et al [34] for municipal wastewater and paper mill effluent, respectively. Dotto et al [35] also confirmed an improved COD removal with increasing settling time using MO coagulant in textile wastewater.…”
Section: Effect Of Mo Dose On Turbidity Bod and Cod Removalsupporting
confidence: 91%
“…Therefore, there was no significant difference for turbidity removal between 150 and 200 mg/L of MO. These results are similar to those obtained by Kayode et al [32], Kane et al [33], and Boulaadjoul et al [34] for municipal wastewater and paper mill effluent, respectively. Dotto et al [35] also confirmed an improved COD removal with increasing settling time using MO coagulant in textile wastewater.…”
Section: Effect Of Mo Dose On Turbidity Bod and Cod Removalsupporting
confidence: 91%
“…Thus, it was concluded that M. oleifera is the most effective natural coagulant and reduced turbidity to a larger extent. Kane et al, (2016) reported removal of turbidity and COD up to 90% and 75% respectively from domestic waste water by using alum and M. oleifera seed powder in the ratio of 50:50 (W/V) as a coagulant.…”
Section: Natural Methods Of Water Treatment or Green Techniques Of Water Treatmentmentioning
confidence: 99%
“…Benzolive (Moringa oleifera L) derived products are also used against malnutrition (Kane et al, 2016). Moringa oil and fresh leaves powders are consumed (Mawouma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%